The Dyadic Goddess and Duotheism in Nodilo’s The Ancient Faith of the Serbs and the CroatsDijadna boginja i duoteizam u Nodilovoj Staroj vjeri Srba i Hrvata - Marjanić, Suzana (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Depending on the primary source that is used in the reconstruction of the Southern Slavic Pantheon, the text considers two possibilities for re/construction of the Southern Slavic goddess. Namely, Helmold’s Chronica Slavorum cites Siwa (Živa) as the Polabian Slavic goddess, while, naturally enough, the Russian goddess Mokoš features in the Chronicle of Nestor. Within the framework of these two possibilities of the extension of the Polabian/Russian goddess - Siwa/Mokoš - to the concept of the Southern Slavic goddess, my intention is to show Nodilo’s re/construction of the Southern Slavic dyadic goddess - the celestial Vida and the terrestrial Živa - or, more precisely, the goddess in the context of the »ancient faith« of the Serbs and the Croats in the chapter entitled »Sutvid and Vida« in Nodilo’s work The Ancient Faith of the Serbs and the Croats (1885-1890). In the re/construction of the assumed duotheism of the theophoric pair of twins - Vid (Svantevid) and Vida/Živa – who create an incestuous hierogamy, Nodilo starts out from Helmold’s Chronicle, which relates to the Baltic Slavs.